Structural characteristics of carbon fiber with ultrahigh tensile strength and high modulus - Xiaoxue Feng; Shuang Li; Yu Wang; Aijun Gao; Yuanjian Tong (Materials Research Express)
To shed light for production of carbon fibers with even better tensile properties, the structure of carbon fiber with ultrahigh tensile strength and high modulus was investigated and compared with M40J using SEM, Raman, XRD and TEM. The tensile strength and modulus of the carbon fiber prepared was 7.677 GPa and 362 GPa respectively, which was the highest combination of tensile strength and modulus for polyacrylonitrile-based carbon fibers up to now. Smooth surface, nearly perfect circular cross-section, irregular lattice structure and low degree of graphitization positively contributed to improve the tensile strength. The tensile strength was also benefited from compact but small crystal size with moderate crystal orientation. The homogeneity of graphite microcrystals in the fiber was beneficial for increasing tensile strength of PAN-based carbon fibers with high modulus.